The monster theory reader - Weinstock, Jeffrey Andrew (University of Minnesota Press, 2020)
"Keeping pace with contemporary Western culture's fascination with monsters, monster theory has attempted to explore the significance of monsters in different genre, media, and cultural contexts; complicating this project however has been the absence of a single volume collecting in one place central approaches and significant works. Monster Theory: A Reader will address this gap and bring together many of the scattered articles, essays, and book chapters theorizing monsters and monstrosity, thereby making the volume extremely useful for researchers and ideal for course adoption for classes involving a focus on monsters"--Provided by publisher.